Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/acel.13252
|View full text |Cite
|
Sign up to set email alerts
|

Elevated miR‐124‐3p in the aging colon disrupts mucus barrier and increases susceptibility to colitis by targeting T‐synthase

Abstract: According to the United Nations 2019 Revision of World Population Prospects, the proportion of people over 65 years of age is expected to increase from approximately 9% in 2019 to nearly 16% in 2050; thus, global population aging is the greatest challenge for further global public health efforts in the future. Aging is a natural process characterized by progressive functional impairment of tissues and organs and even pathophysiological changes. In particular, the gastrointestinal (GI) tract is greatly impacted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 40 publications
(65 reference statements)
6
27
0
Order By: Relevance
“…The procedure used to generate the DSS colitis model is shown in Supplementary Figure 1A . Our published data 12 demonstrated that miR-1-3p expression in the distal colon mucosa of 24-mo-old mice was 1.6 times higher than that of miR-124-3p . These previous data provide a reference for the miRNA agomir dose required in the animal model.…”
Section: Methodsmentioning
confidence: 70%
See 1 more Smart Citation
“…The procedure used to generate the DSS colitis model is shown in Supplementary Figure 1A . Our published data 12 demonstrated that miR-1-3p expression in the distal colon mucosa of 24-mo-old mice was 1.6 times higher than that of miR-124-3p . These previous data provide a reference for the miRNA agomir dose required in the animal model.…”
Section: Methodsmentioning
confidence: 70%
“…8 , 9 As one of the hallmarks of health, 10 the intestinal barrier is progressively damaged during senescence. 11 Our recent work 12 demonstrated that age-related changes in mucus properties increase the susceptibility to colitis in elderly populations. However, research on the underlying regulatory mechanism is far from comprehensive.…”
Section: Introductionmentioning
confidence: 99%
“…The intestinal mucosal barrier integrity is necessary to maintain normal intestinal functions ( Huang et al, 2020 ). The thick mucus covering the epithelium is the primary defensive layer separating microbiota from epithelial cells, which is synthesized by goblet cells ( Johansson and Hansson, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gel-forming mucin2 (Muc-2) is the major building block of mucus, which accounts for up to 80% of the mass of mucin molecules, and Muc-2 is the reason for the gel-like properties of mucus ( Johansson et al, 2008 ; Fu et al, 2011 ). Moreover, the intestinal gel-forming mucins are mainly from goblet cells ( Huang et al, 2020 ). In our study, a fewer goblet cells number, thinner AB/PAS mucus layer, and lower Muc-2 protein expression in the colonic tissue of STC rats were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, miR-124-3p was reported to target T-synthase, also known as C1GALT1, which catalyses the core-1 O-glycosylation of mucins. The miR-124-3p-mediated downregulation of T-synthase interferes with mucin O-glycosylation, leading to a predisposition for senile colitis [ 140 ]. The expression of C1GALT1 is dependent on a specific molecular chaperon, C1GALT1C1 (Cosmc).…”
Section: Permeability Of the Gut Epithelial Barriermentioning
confidence: 99%